Radiation therapy related cardiac disease risk in childhood cancer survivors: Updated dosimetry analysis from the Childhood Cancer Survivor Study. (October 2021) - Shrestha, Suman; Bates, James E.; Liu, Qi; Smith, Susan A.; Oeffinger, Kevin C.; Chow, Eric J.; Gupta, Aashish C.; Owens, Constance A.; Constine, Louis S.; Hoppe, Bradford S.; Leisenring, Wendy M.; Qiao, Ying; et al.
Highlights: Radiation-related late cardiac disease risk is updated for the Childhood Cancer Survivor Study using enhanced dosimetry. Consistent with previous findings, late cardiac disease risk increases with Dm ≥ 10 Gy, V20 ≥ 0.1%, and V 5, V 20 = 0 % ≥ 50%. Risks are significantly ( P < 0.05) higher than previously estimated for survivors with Dm in the range of 20–29.9 Gy. Risks are significantly ( P < 0.05) higher than previously estimated for survivors with V20 in the range of 30–79.9%. Abstract: Background and purpose: We previously evaluated late cardiac disease in long-term survivors in the Childhood Cancer Survivor Study (CCSS) based on heart radiation therapy (RT) doses estimated from an age-scaled phantom with a simple atlas-based heart model (HAtlas ). We enhanced our phantom with a high-resolution CT-based anatomically realistic and validated age-scalable cardiac model (HHybrid ). We aimed to evaluate how this update would impact our prior estimates of RT-related late cardiac disease risk in the CCSS cohort. Methods: We evaluated 24, 214 survivors from the CCSS diagnosed from 1970 to 1999. RT fields were reconstructed on an age-scaled phantom with HHybrid and mean heart dose (Dm ), percent volume receiving ≥ 20 Gy (V20 ) and ≥ 5 Gy with V20 = 0 ( V 5, V 20 = 0 % ) were calculated. We reevaluated cumulative incidences and adjusted relative rates of grade 3–5 Common Terminology Criteria for Adverse Events outcomes for any cardiac disease, coronary artery disease (CAD), and heart failure (HF) in association with Dm, V20, and V 5, V 20 = 0 % (as categorical variables). Dose-response relationships were evaluated using piecewise-exponential models, adjusting for attained age, sex, cancer diagnosis age, race/ethnicity, time-dependent smoking history, diagnosis year, and chemotherapy exposure and doses. For relative rates, Dm was also considered as a continuous variable. Results: Consistent with previous findings with HAtlas, reevaluation using HHybrid dosimetry found that, Dm ≥ 10 Gy, V20 ≥ 0.1%, and V 5, V 20 = 0 % ≥ 50% were all associated with increased cumulative incidences and relative rates for any cardiac disease, CAD, and HF. While updated risk estimates were consistent with previous estimates overall without statistically significant changes, there were some important and significant ( P < 0.05) increases in risk with updated dosimetry for Dm in the category of 20 to 29.9 Gy and V20 in the category of 30% to 79.9%. When changes in the linear dose–response relationship for Dm were assessed, the slopes of the dose response were steeper ( P < 0.001) with updated dosimetry. Changes were primarily observed among individuals with chest-directed RT with prescribed doses ≥ 20 Gy. Conclusion: These findings present a methodological advancement in heart RT dosimetry with improved estimates of RT-related late cardiac disease risk. While results are broadly consistent with our prior study, we report that, with updated cardiac dosimetry, risks of cardiac disease are significantly higher in two dose and volume categories and slopes of the Dm-specific RT-response relationships are steeper. These data support the use of contemporary RT to achieve lower heart doses for pediatric patients, particularly those requiring chest-directed RT.